Trisomy 21 Testing in Second Trimester: Reliability Comparison of Triple and Quadruple Testing in Pakistan - Shumaila Yasin, Sarfraz Ahmed, Mariya Shahbaz, Sabeena Umer, Shazia Roman, Faiza Irshad (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: Down syndrome is a disorder that affects one in every 700 babies born, and it is one of the most frequent causes of developmental delay (DS). In Pakistan, prenatal screening for Down syndrome is not being practised according to any approved protocol. The biochemical screening that takes place during the second trimester is still carried out using the triple test. Although the quadruple test has a better sensitivity and specificity than other diagnostic methods, its usage in routine medical settings is not advised. The purpose of this study was to explore the second trimester screening for trisomy 21 (quadruple test with genetic sonogram) in order to determine its sensitivity and accuracy in comparison to biochemical testing. Place of Study: District Headquarters Hospital, Gujranwala Duration of Study: January 2021 to December 2021 Methods: This retrospective observational study was carried out in a Fetal Medicine Centre with the purpose of analysing the odds of being affected with Down syndrome, given a positive risk (OAPR) upon screening in the quadruple test; triple test and quadruple test plus a genetic sonogram for highrisk singleton pregnancies (in view of advanced maternal age; an anomaly scan showing some abnormality, etc.). Given the presence of a positive risk factor, the goal of this study was to ascertain the likelihood of having a child impacted by Down syndrome. Practical Implication: To explore the second trimester screening for trisomy 21 (quadruple test with genetic sonogram) in order to determine its sensitivity and accuracy in comparison to biochemical testing. Results: The discovery of trisomies was made after an investigation into 3,042 highrisk pregnancies with a singleton baby. 327 pregnant women who have received positive findings from a triple test, quadruple test, or quadruple test in addition to a genetic ultrasonography opt to have an amniocentesis. This decision was made after the ladies learned that their unborn child may have a genetic disorder. It was discovered that 20 of the developing babies were affected by Down syndrome. The OAPR for the quadruple test was demonstrated to be significantly higher when compared to the OAPR for the triple test (1:29.1 as compared to 1:39.2). It was found that the combination of the triple test and the genetic sonogram had the highest OAPR of 1:7. Conclusions: The triple test combined with a genetic sonogram is the most effective tool for screening for trisomy 21, and it has the potential to cut down on the number of unnecessary amniocentesis operations carried out in high-risk populations. Keywords: Down syndrome, genetic, quadruples test, second trimester screening, triple test,ultrasound